Strategi Daya Tindak Versi Bahasa Melayu - Salhah Abdullah (Universiti Sains Islam Malaysia, 2016)
This study aims to make the Coping strategies inventory adapt to the Malay language. The aim is to test the trusted ability of the inventory and to translate it so that it is relevant to the various cultures which experience stress in Malaysia. The method employed is based upon a case study of 100 students in a school for the initial study and towards 140 female students in two juvenile detention centers. These studies have shown a consistency with the findings of past studies in Spain. Psychometric features demonstrate an interesting find because eight of the factors from 40 items which is studied in Spain had also showed the alfa Cronbach coeficient value that is high for eight factors i.e. between .61 to .76. The alfa Cronbach value for ISDT that is high i.e. 0.93 indicate the relevancy of the inventory used.